Holt physical science - William L Ramsey [et al.] (Holt, Rinehart and Winston, 1988)
The book consists of 21 chapters organized into six units. The first chapter presents science and some of the tools scientists use to solve problems. The three units following chapter 1 are concerned with physics, the study of energy. The last three units deal with chemistry, the study of matter. Each unit contains several chapters that begin with a chapter goals. Each chapter is further divided into several sections that begin with a list of section objectives. Each section ends with a brief summary of the important adeas developed in the section. Questions at the end of the section help to test